Mind the gender gap in ride-hailing from the demand side. (February 2023) - Qiao, Si; Zhang, Mengzhu; Yeh, Anthony Gar-On
Abstract: Improving the transport system to enhance women's access to social opportunities and services has been a key initiative in mitigating gender inequality. Studies have examined women's different travel demands and experiences from men, and the mismatch between women's demands and transport services. However, little attention has been given to the gender gap in ride-hailing usage in the context of the fast development of platform economy-based new transportation services. Thus, this paper examines the nexus between gender and inequalities in ride-hailing from the demand side. Two key questions are explored: if ride-hailing serves women more/less, how does this gender difference in using ride-hailing occur? Does the emergence of ride-hailing mitigate or deteriorate the existing gender gap in capability to move? An innovative integration of big data and time-space geography approaches is developed to examine the multi-source data collected from Chengdu, China. The modelling results indicate that ride-hailing emerges as an affordable travel mode addressing women's demand for long-distance travel in the Chinese context of women's high labour participation and thus the existence of a considerable number of employed women with a sizeable daily activity space and a considerable income. The gender gap in capability to move is thus mitigated by ride-hailing at an aggregate level. This paper calls for a more nuanced and context-specific understanding of how ride-hailing may provide challenges and opportunities to gender equity in daily travel.